1988
DOI: 10.1590/s0036-46651988000100005
|View full text |Cite
|
Sign up to set email alerts
|

Aportes al conocimiento de la hidatidosis como zoonosis urbana

Abstract: RESUMENEn la República Argentina, la hidatidosis constituye un serio problema que afecta a la salud publica y tiene graves repercusiones socioeconómicas.Las fuertes corrientes urbanisticas han traido consigo el traslado de algunas costumbres rurales hacia los centros poblados. A partir ae ello la hidatidosis en las areas endêmicas ha adquirido importância como zoonosis urbana.Si bien las cifras de infección canina halladas (1.12%) son significativamente inferiores que en las áreas rurales de la misma región, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
1
1
Order By: Relevance
“…The high values of positive feces in Cipolletti are remarkable because this species is not considered endemic in the north of the province and therefore not included in monitoring or control programs (Mujica et al 2021). Higher values in urban echinococcosis in Cipolletti (13.3%) has been observed in this work compared with an infection percentage of 1.69 detected by arecoline purgation recorded 30 years ago (Larrieu et al 1988). However, it has been reported that the sensitivity of arecoline purgation is less than the copro-ELISA analysis (Pierangeli et al 2010).…”
Section: Discussioncontrasting
confidence: 48%
“…The high values of positive feces in Cipolletti are remarkable because this species is not considered endemic in the north of the province and therefore not included in monitoring or control programs (Mujica et al 2021). Higher values in urban echinococcosis in Cipolletti (13.3%) has been observed in this work compared with an infection percentage of 1.69 detected by arecoline purgation recorded 30 years ago (Larrieu et al 1988). However, it has been reported that the sensitivity of arecoline purgation is less than the copro-ELISA analysis (Pierangeli et al 2010).…”
Section: Discussioncontrasting
confidence: 48%
“…Na Argentina, mais precisamente na Patagônia, no período de 1984 e 1985, foi registrada uma prevalência de 1,12% de equinococose canina urbana (LARRIEU, et al, 1988). Conforme relatos de CARDOSO et al (1995), na cidade de Melo (Uruguai), de 51% dos cães capturados no período de 8/9 à 22/10 de 1992, em bairros urbanos e suburbanos, 4,4% eram portadores do parasita.…”
Section: Introductionunclassified